Pengaruh Penambahan Cacahan Limbah Plastik HDPE (High Density Polyethylene) Sebagai Bahan Tambah Campuran Laston AC-WC (Asphalt Concrete-Wearing Course) Terhadap Karakteristik Marshall - Ndun, Kezia Dwi Putri Natalia; Koreh, Andreas Welem; Lamdu, Anita Kurniati Alachmad (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
In increase quality vulnerable roads in Indonesia damaged Because influenced by weather, water, load vehicle excess, and construction insufficient pavement​ fulfil requirements, required material add as much as you can increase strength and help repair construction road asphalt the Utilization material waste plastic in construction pavement become good alternative​ in in increase quality pavement road. Objective study This is For know How influence addition waste plastic type High Density Polyethylene (HDPE) against Marshall Laston AC-WC characteristics with variation rate HDPE plastic at 0%, 2%, 4%, and 6%. Marshall characteristics reviewed is mark density (density), VIM (void in mix), VMA (void mineral aggregate), VFA (void filled with asp halt), melting (flow), and stability. Method research used​ with method experiments in the laboratory and refers to Specification General Highways​ 2018. Research results shows the Marshall test on the mixture Laston AC-WC with addition rate HDPE plastic 0%, 2%, 4%, and 6% can be raise mark density (density), stability , VFA ( Void Filled with Asphalt), whereas For VIM (void in mix), VMA (Void Mineral Aggregate) and melt (flow) values experienced decline . Marshall parameter values obtained​​ fulfil standard Specification General Highways​ 2018. Percentage​ rate optimum asphalt (KAO) obtained is 6.0%, Marshall test of variation material plus waste plastic best value​ For density, melting (flow), stability, VIM , VMA, and VFA, namely at levels waste plastic 2%.